Evidence-Based Practices in the Cardiac Catheterization Laboratory: A Scientific Statement From the American Heart Association. Issue 5 (3rd August 2021) - Bangalore, Sripal; Barsness, Gregory W.; Dangas, George D.; Kern, Morton J.; Rao, Sunil V.; Shore-Lesserson, Linda; Tamis-Holland, Jacqueline E.
Abstract : Cardiac catheterization procedures have rapidly evolved and expanded in scope and techniques over the past few decades. However, although some practices have emerged based on evidence, many traditions have persisted based on beliefs and theoretical concerns. The aim of this review is to highlight common preprocedure, intraprocedure, and postprocedure catheterization laboratory practices where evidence has accumulated over the past few decades to support or discount traditionally held practices.